On various Superstitions in the North-West Highlands and Islands of Scotland, especially in relation to Lunacy (Proceedings of the Society of Antiquaries of Scotland, 1862)
Arthur Mitchell discusses several sites, rituals and superstitions in the Highlands and Islands that are alleged to have curative properties for those suffering from various forms of mental illness. He argues that these beliefs may be remnants of a pre-Christian religion. He also discusses anecdotal and written evidence of other treatments for mental illness that are motivated by the association between mental illness and demonic possession. There is also discussion of the burial rites of people who took their own life. Mitchell is critical of all these practices but reminds his audience that similar cures had been used within living memory at the time of writing and some were even still in use.